The Effect of Replacing Flour with Seaweed (Eucheuma cottonii) on Fiber Content and How Much Chicken Meatballs Are Liked - Sely Putri Hermawita; Radella Hervidea; Asep Jalaludin (Jurnal Kesehatan Cendikia Jenius, 2026)
University students are a productive age group vulnerable to obesity due to low dietary fiber intake, highlighting the need for functional food innovations that improve fiber consumption while maintaining consumer acceptability. This study aimed to analyze the effect of Eucheuma cottonii seaweed flour substitution on the crude fiber content and organoleptic properties of chicken meatballs as an alternative high-fiber snack. This experimental study employed a Completely Randomized Design (CRD) with four treatment groups (P0, P1, P2, and P3). Organoleptic evaluation was conducted involving 25 student panelists in May 2025, while proximate analysis included moisture, ash, protein, fat, crude fiber, and carbohydrate contents. Data were analyzed using ANOVA and SPSS. The results showed that the P2 formulation (10 g seaweed flour) achieved the highest acceptability scores for color, aroma, texture, and taste (p<0.05). Crude fiber content increased from 2.72% to 4.20%, accompanied by increased ash and carbohydrate contents and reduced moisture, protein, and fat levels. Substitution with 10 g of Eucheuma cottonii seaweed flour has the potential to improve the nutritional quality and consumer acceptability of chicken meatballs. Further studies should evaluate shelf life, physical characteristics, and other nutritional components.